The Effect of Lemon Juice and CMC Addition on Yellow Pumpkin Fruit Leather Characteristics - Khasanah, Mulidati Mutya; Aviana, Devi Nurul; Rofiah, Aliyatur; Muflihati, Iffah; Affandi, Arief Rahman (FoodTech: Jurnal Teknologi Pangan, 2025)
Pumpkin is a fruit that has the potential to be developed into a food product with high economic value. One of the food products is fruit leather with the addition from carboxy methyl cellulose (CMC) and lemon. This study aims to determine the effect of the concentration of addition of lemon juice and concentration of carboxy methyl cellulose on the characteristics of pumpkin. The method used was Factorial Completely Randomized Design with 2 factors, namely the concentration of lemon juice (25% and 12.5%) and the concentrations of it carboxy methyl cellulose (1% and 2%). The resulting fruit leather was observed for its quality including water content, total acidity, pH, descriptive tests including yellow color, sour taste, and texture, and hedonic values of color, taste and texture. The results showed that the addition carboxy methyl cellulose and lemon juice had an effect on water content, total acid, pH and organoleptic properties in both descriptive and hedonic tests. The best treatment based on hedonic and descriptive tests is on fruit leather with 5% lemon juice and 1% carboxy methyl cellulose. Based on chemical characteristics produce pumpkin skin with a moisture content of 11.46%, total acid 0.85%, pH 4.57%.